Spotlight on data the power of deep learning in the hands of domain experts - Howard, Jeremy (O'Reilly Media, 2019)
"In this Spotlight on Data, find out how Silicon Valley Innovation Laboratories, a research center established by Japanese electric and electronics equipment company Furukawa Electric, trained a deep learning model to recognize manufacturing defects in fiber optic cables using platform.ai, without writing any code or needing the help of a data scientist."--Resource description page
Title from title screen (viewed February 19, 2020)
Keywords: Machine learning; Big data; Business enterprises -- Data processing; Apprentissage automatique; Données volumineuses; Entreprises; Informatique; Business enterprises; Data processing; Electronic videos